Eighteen years of paediatric extracorporeal membrane oxygenation and ventricular assist devices: insight regarding late outcomes. (17th September 2018) - Shah, Shawn M.; Kays, David W.; Ghazarian, Sharon R.; Karl, Tom R.; Alexander, Plato; Sznycer-Taub, Nathaniel; Parker, Jason; Oldeen, Molly; Almodovar, Melvin C.; Stapleton, Gary; Quintessenza, James A.; Asante-Korang, Alfred; et al.
Abstract: Background: We reviewed all patients who were supported with extracorporeal membrane oxygenation and/or ventricular assist device at our institution in order to describe diagnostic characteristics and assess mortality. Methods: A retrospective cohort study was performed including all patients supported with extracorporeal membrane oxygenation and/or ventricular assist device from our first case (8 October, 1998) through 25 July, 2016. The primary outcome of interest was mortality, which was modelled by the Kaplan–Meier method. Results: A total of 223 patients underwent 241 extracorporeal membrane oxygenation runs. Median support time was 4.0 days, ranging from 0.04 to 55.8 days, with a mean of 6.4±7.0 days. Mean (±SD) age at initiation was 727.4 days (±146.9 days). Indications for extracorporeal membrane oxygenation were stratified by primary indication: cardiac extracorporeal membrane oxygenation (n=175; 72.6%) or respiratory extracorporeal membrane oxygenation (n=66; 27.4%). The most frequent diagnosis for cardiac extracorporeal membrane oxygenation patients was hypoplastic left heart syndrome or hypoplastic left heart syndrome-related malformation (n=55 patients with HLHS who underwent 64 extracorporeal membrane oxygenation runs). For respiratory extracorporeal membrane oxygenation, the most frequent diagnosis was congenital diaphragmatic hernia (n=22). A total of 24 patients underwent 26 ventricular assist device runs. Median support time was 7 days, ranging from 0 to 75 days, with a mean of 15.3±18.8 days. Mean age at initiation of ventricular assist device was 2530.8±660.2 days (6.93±1.81 years). Cardiomyopathy/myocarditis was the most frequent indication for ventricular assist device placement (n=14; 53.8%). Survival to discharge was 42.2% for extracorporeal membrane oxygenation patients and 54.2% for ventricular assist device patients. Kaplan–Meier 1-year survival was as follows: all patients, 41.0%; extracorporeal membrane oxygenation patients, 41.0%; and ventricular assist device patients, 43.2%. Kaplan–Meier 5-year survival was as follows: all patients, 39.7%; extracorporeal membrane oxygenation patients, 39.7%; and ventricular assist device patients, 43.2%. Conclusions: This single-institutional 18-year review documents the differential probability of survival for various sub-groups of patients who require support with extracorporeal membrane oxygenation or ventricular assist device. The indication for mechanical circulatory support, underlying diagnosis, age, and setting in which cannulation occurs may affect survival after extracorporeal membrane oxygenation and ventricular assist device. The Kaplan–Meier analyses in this study demonstrate that patients who survive to hospital discharge have an excellent chance of longer-term survival.